On the fatigue behavior of support structures for offshore wind turbines - Alati N.; Nava V.; Failla G.; Arena F.; Santini A. (Wind and Structures, 2014)
It is believed that offshore wind farms may satisfy an increasing portion of the energy demand in the next years. This paper presents a comparative study of the fatigue performances of tripod and jacket steel support structures for offshore wind turbines in waters of intermediate depth (20-50 m). A reference site at a water depth of 45 m in the North Atlantic Ocean is considered. The tripod and jacket support structures are conceived according to typical current design. The fatigue behavior is assessed in the time domain under combined stochastic wind and wave loading and the results are compared in terms of a lifetime damage equivalent load. Copyright © 2014 Techno-Press, Ltd.